Preparation method of high-entropy Prussian blue analogue material CuCoNiCrMn-PBA
CuCoNiCrMn-PBA, a high-entropy Prussian blue analog material prepared by co-precipitation method and Oswald maturation process, solved the problem of cycle stability caused by the Jahn-Teller effect of the active metal element Mn, and realized the positive electrode material of sodium ion battery High specific capacity and excellent cycle stability, and simple process, safe and efficient.
Patent Information
- Application Number
- CN202411836619.6
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-12-13
- Publication Date
- 2025-01-10
- Estimated Expiration
- 2044-12-13
AI Technical Summary
The existing sodium ion battery positive electrode materials show poor cycle stability due to the Jahn-Teller effect of the active metal element Mn, making it difficult to achieve a large-capacity battery material that is rapidly embedded/detached.
CuCoNiCrMn-PBA, a high-entropy Mn-pyprus blue analog material, was prepared by co-precipitation method and Oswald's maturation process, using sodium citrate as chelating agent and ascorbic acid As a reducing agent, the Jahn-Teller effect of the Mn element is inhibited to form an open and stable framework structure.
The high-entropy Prussian blue analog material has been prepared, with excellent cycle stability and specific capacity, and is suitable for sodium ion battery positive electrode material, with simple operation, high safety, high yield, and good consistency of the material morphology.
Smart Images

Figure CN119284924A_ABST
Abstract
Description
Technical Field
[0001] The present invention relates to the technical field of sodium ion batteries, and particularly to a preparation method of a high-entropy Prussian blue analogue material CuCoNiCrMn-PBA. Background Art
[0002] In the past few decades, the successful development of high-capacity and cycle-stable lithium intercalation materials has enabled the rapid commercial application of lithium ion batteries (LIBs), ranging from portable electronic products to electric vehicles and smart grids. However, with the large-scale use of lithium ion batteries in large-scale electrical energy storage (EES) applications, there are serious concerns about the rapidly rising cost and scarce resources of global lithium ion battery reserves. To address this challenge, in recent years, great attention has been paid to finding low-cost and material-rich LIBs alternatives for emerging EES applications. In this regard, sodium ion batteries (SIBs) seem to be an ideal choice due to the wide availability and low cost of sodium resources. As early as the 1980s, researchers have already conducted certain research on the insertion reaction of sodium ions, but for a long time, no main battery materials with large specific capacity that can perform rapid sodium ion insertion / extraction have been found.
[0003] Among several reported cathode materials, Prussian blue analogues (PBAs) are a class of hexaferrocyanates with a perovskite-type, face-centered cubic structure (space group Fm-3m). It can be expressed as A x M[Fe(CN) 6 y ·zH2O, where A is an alkali metal ion such as Li + , Na + , K + ; M represents transition metal ions such as Fe, Mn, Co, Ni, Mn, Cu, etc.; 0 < x < 2; 0 < y < 1. Compared with transition metal oxides and phosphates, the PBA lattice has a relatively large interstitial "A" site (diameter 4.6 Å) and a spacious channel (diameter 3.2 Å, <100> direction), so it has a high diffusion coefficient of 10 -9 ~10 -8 cm 2 s -1 . Therefore, the ionic conductivity of its lattice is much higher. The reversible regulation of the large-channel structure and the convenient transportation of large Na + ions enable electrochemical insertion reactions. Nevertheless, Prussian blue-based materials exhibit poor cycle stability due to the Jahn-Teller effect of their active metal elements (such as Mn). Summary of the Invention
[0004] The purpose of the present invention is to overcome the deficiencies of the prior art and provide a method for preparing a high entropy Prussian blue analog material CuCoNiCrMn-PBA. The present invention uses a variety of transition metal sulfates and sodium ferrocyanide as raw materials, sodium citrate as a chelating agent, and ascorbic acid as a reducing agent, and obtains a high entropy Mn-based Prussian blue analog material in which a variety of elements are coordinated with N atoms through coprecipitation and Oswald ripening. The multiple transition metal elements suppress the Jahn-Teller effect of the Mn element while providing capacity, and have an open and stable framework structure. The method has the advantages of simple operation, high safety, and high yield.
[0005] To achieve the above purpose, the technical solution designed by the present invention is as follows: The present invention provides a method for preparing a high entropy Prussian blue analog material CuCoNiCrMn-PBA, comprising the following steps: (1) dissolving copper salt, cobalt salt, nickel salt, chromium salt, manganese salt and sodium citrate in deionized water, adjusting the pH to 2-3, and obtaining a transition metal solution; (2) dissolving sodium ferrocyanide and sodium chloride in deionized water to obtain a sodium ferrocyanide salt solution; (3) adding the transition metal solution and the sodium ferrocyanide salt solution dropwise into deionized water while stirring to perform co-precipitation; (4) After the coprecipitation is completed, ascorbic acid is added to obtain a mixture; (5) The mixture is subjected to an Oswald ripening process and centrifuged to obtain a precipitate, thereby obtaining a high entropy Prussian blue analog material CuCoNiCrMn-PBA.
[0006] Furthermore, the conditions of the Oswald ripening process are: the mixture is placed in an environment of 60-100°C for 24 hours; The particle size of the high entropy Prussian blue analog material CuCoNiCrMn-PBA is 0.5-1 μm.
[0007] Furthermore, in step (1), the molar concentration of the transition metal element is 2.625-4.2 mmol / L, and the molar ratio of the copper salt, the cobalt salt, the nickel salt, the chromium salt and the manganese salt in the transition metal element is 1:1:1:1:1-4; The molar ratio of transition metal element to sodium citrate is 1:3-5; The pH was adjusted to 3 using 0.1 mol / L dilute hydrochloric acid.
[0008] Furthermore, in the transition metal solution, the molar concentration of the transition metal element is 3 mmol / L, and among the transition metal elements, the molar ratio of the copper salt, the cobalt salt, the nickel salt, the chromium salt and the manganese salt is 1:1:1:1:1.71; The molar ratio of the transition metal element to sodium citrate is 1:5.
[0009] Furthermore, the copper salt is copper sulfate pentahydrate, the cobalt salt is cobalt sulfate heptahydrate, the nickel salt is nickel sulfate hexahydrate, the chromium salt is chromium sulfate hexahydrate, and the manganese salt is manganese sulfate monohydrate.
[0010] Furthermore, in the step (2), the molar ratio of sodium ferrocyanide to sodium chloride is 1:20-25, and the molar ratio of the transition metal element to sodium ferrocyanide is 1:1.2-2.
[0011] Furthermore, the molar ratio of the sodium ferrocyanide to sodium chloride is 1:25, and the molar ratio of the transition metal element to sodium ferrocyanide is 1:1.6.
[0012] Furthermore, in the step (3), the dripping speed is 1 drop per second, and 3 to 5 drops of sodium ferrocyanide salt solution are first dripped, and then the transition metal solution and the sodium ferrocyanide salt solution are dripped simultaneously; In the step (4), the molar ratio of ascorbic acid to transition metal element is 3.79:1.
[0013] The present invention also provides an electrode sheet, which comprises the high entropy Prussian blue analog material CuCoNiCrMn-PBA prepared by the preparation method.
[0014] The present invention also provides a sodium ion battery, which comprises the electrode sheet.
[0015] Principle of the present invention: 1. High entropy materials have an inhibitory effect on the Jahn-Teller effect of the Mn element. The present invention uses a transition metal Cr containing multiple valence states, which can provide partial capacity while inhibiting the dissolution of Mn.
[0016] 2. When the chelating agent (sodium citrate) is added to the mixed solution containing metal ions, the precipitant reacts with the metal ions. For example, ferrocyanide ions ([Fe (CN) 6 ] 4- ) combines with other metal ions (such as copper ions, cobalt ions, etc.) through electrostatic attraction and coordination to form a precipitate of Prussian blue analogues.
[0017] 3. The present invention selects 60-100°C to perform the Oswald ripening process on the generated precipitate and solution. When the ambient temperature rises, 1) the concentration of the solute in the solution is more likely to reach a supersaturated state, thereby accelerating the deposition process of the solute on the surface of the large particles and accelerating the speed of Oswald ripening; 2) when the temperature rises, the diffusion speed of the metal ions in the solution is accelerated, shortening the time for small particles to diffuse into large particles and accelerating the rate of Oswald ripening.
[0018] According to the Kelvin equation, the radius of curvature of a particle is related to the chemical potential. The smaller the radius of curvature (i.e., the smaller the particle), the higher the chemical potential. This means that small particles have a greater tendency to dissolve in the solvent because they have a higher energy state and tend to reduce their own energy by dissolving. Due to the instability and higher chemical potential of small particles, the molecules on the surface will gradually break away from the small particles and dissolve into the surrounding solvent, causing the small particles to shrink continuously. In this process, the concentration of solute molecules in the solvent gradually increases. When the concentration of solute molecules in the solvent reaches a supersaturated state, they tend to re-deposit in areas with lower energy, that is, on the surface of large particles. Because large particles have lower surface energy and can provide more stable binding sites, solute molecules are more likely to attach and grow on large particles. Over time, solutes dissolved from small particles are continuously deposited on large particles, causing large particles to continue to grow, while small particles gradually shrink and disappear. Ultimately, the particle size distribution of the entire system will change, and the average particle size will gradually increase. This makes the product structure more stable.
[0019] Beneficial effects of the present invention: 1. The present invention is easy to operate: The coprecipitation method is simple to operate. It only requires that the metal sulfate and sodium ferrocyanide to be introduced are separately prepared into solutions, and then deionized water is added at the same time to obtain precipitation.
[0020] 2. The present invention has high production efficiency: in the coprecipitation process, the reaction is relatively complete, the drug loss is small, the precipitation amount is large, and the yield is high.
[0021] 3. The product of the present invention has high consistency in morphology: the synthesized high entropy Prussian blue analogue CuCoNiCrMn-PBA presents a regular and uniform cube.
[0022] 4. The present invention regulates the pH value of the transition metal solution to be acidic, thereby ensuring that no other precipitation reactions occur before the metal ions are co-precipitated.
[0023] 5. The present invention reduces the release rate and concentration of metal elements in the coprecipitation solution system through multiple steps, reduces the reaction rate, and ensures the introduction of multiple metal elements.
[0024] 6. The present invention maintains the added transition metal ions in a low valence state by adding ascorbic acid (reducing agent), thereby providing a certain capacity in the subsequent half-cell test.
[0025] 7. The present invention stabilizes the structure of the Prussian blue analogue by performing Oswald ripening at high temperature, thereby improving the cyclic stability of the material.
[0026] In summary, the present invention obtains a high-entropy Prussian blue analog CuCoNiCrMn-PBA with a regular cubic morphology by combining a coprecipitation reaction and an Oswald ripening process. This method can be generally used in the preparation process of multi-element doped Prussian blue analogs. And through its electrochemical performance test, it is found that the specific capacity and cycle stability of the material are in line with expectations, and it can be used as a positive electrode material for sodium ion batteries. BRIEF DESCRIPTION OF THE DRAWINGS
[0027] Figure 1 This is a SEM image of the high entropy Prussian blue analog CuCoNiCrMn-PBA prepared in Example 1; Figure 2 This is a SEM image of the Prussian blue analog CuCoNiCrMn-PBA prepared in Comparative Example 1; Figure 3 The CV curve of the high entropy Prussian blue analog CuCoNiCrMn-PBA prepared in Example 1 as a positive electrode active material for a sodium ion battery in a half-cell; Figure 4 The CV curve of the Prussian blue analog CuCoNiCrMn-PBA prepared in Comparative Example 1 as a positive electrode active material for a sodium ion battery in a half-cell; Figure 5 Cycling performance diagram of the high entropy Prussian blue analog CuCoNiCrMn-PBA prepared in Example 1 as a positive electrode active material for sodium ion batteries in a half-cell (100 mA g -1 ); Figure 6 Cycling performance diagram of the high entropy Prussian blue analog CuCoNiCrMn-PBA prepared in Example 1 as a positive electrode active material for sodium ion batteries in a half-cell (1 A g -1 ); Figure 7 Cycling performance diagram of the Prussian blue analog CuCoNiCrMn-PBA prepared in Comparative Example 1 as a positive electrode active material for sodium ion batteries in a half-cell (100 mA g -1 ); Figure 8 Cycling performance diagram of the Prussian blue analog CuCoNiCrMn-PBA prepared in Comparative Example 1 as a positive electrode active material for sodium ion batteries in a half-cell (1 A g -1 ); Fig. 9 This is a rate performance diagram of the high entropy Prussian blue analog CuCoNiCrMn-PBA prepared in Example 1 as a positive electrode active material for a sodium ion battery in a half-cell; Fig.10This is a rate performance diagram of the Prussian blue analogue CuCoNiCrMn-PBA prepared in Comparative Example 1 as a positive electrode active material for a sodium ion battery in a half-cell. DETAILED DESCRIPTION
[0028] The present invention is further described in detail below in conjunction with specific embodiments so that those skilled in the art can understand.
[0029] Example 1 This embodiment provides a method for preparing a high entropy Prussian blue analog material CuCoNiCrMn-PBA, comprising the following steps: 1. Take 0.525 mmol CuSO 4 •5H 2 O, 0.525 mmol CoSO 4 •7H 2 O, 0.525 mmol NiSO 4 •6H 2 O, 0.525 mmol Cr 2 (SO 4 ) 3 6H 2 O, 0.9 mmol MnSO 4 •H 2 O and 15 mmol sodium citrate were dissolved in 60 mL deionized water, and the pH of the solution was adjusted to 3 with 0.1 mol / L dilute hydrochloric acid to obtain a transition metal solution; 2. Take 4.8 mmol sodium ferrocyanide and 120 mmol NaCl and dissolve them in 60 mL deionized water to obtain a sodium ferrocyanide salt solution; 3. Add the transition metal solution and sodium ferrocyanide solution to 300 mL of deionized water at a rate of 1 drop per second (add while stirring, first add 3 to 5 drops of sodium ferrocyanide solution and then add the transition metal solution and sodium ferrocyanide solution at the same time) for co-precipitation; 4. After the coprecipitation is completed, add 11.36 mmol ascorbic acid and continue stirring to obtain a mixture; 5. The mixture was placed in an environment of 80°C for 24 h for Oswald ripening. The precipitate obtained by centrifugation was the high entropy Prussian blue analog material with a particle size of 0.5~1 μm.
[0030] The configurational entropy of the high entropy Prussian blue analog material prepared in this example is S conf = 1.7R, its configuration entropy is greater than 1.5R, and it is a high entropy material.
[0031] Example 2 The preparation method of the high entropy Prussian blue analog CuCoNiCrMn-PBA in this embodiment is basically the same as that in Example 1, except that in step 5, the mixture is placed at 60°C for 24 h for Oswald ripening, and the particle size is 0.5-1 μm. The configurational entropy of the high entropy Prussian blue analog material prepared in this embodiment is S conf = 1.65R, its configuration entropy is greater than 1.5R, and it belongs to high entropy material.
[0032] Example 3 The preparation method of the high entropy Prussian blue analog CuCoNiCrMn-PBA in this embodiment is basically the same as that in Example 1, except that in step 5, the mixture is placed at 100°C for 24 h for Oswald ripening, and the particle size is 0.5-1 μm. The configurational entropy of the high entropy Prussian blue analog material prepared in this embodiment is S conf = 1.57R, its configuration entropy is greater than 1.5R, and it belongs to high entropy material.
[0033] Example 4 The preparation method of the high entropy Prussian blue analog CuCoNiCrMn-PBA in this embodiment is basically the same as that in Example 1, except that the amounts of some components are different, as shown in Table 1. The configurational entropy of the high entropy Prussian blue analog material prepared in this embodiment is S conf = 1.65R, its configuration entropy is greater than 1.5R, and it belongs to high entropy material.
[0034] Table 1 Ingredients and dosage
[0035] Example 5 The preparation method of the high entropy Prussian blue analog CuCoNiCrMn-PBA in this embodiment is basically the same as that in Example 1, except that the amounts of some components are different, as shown in Table 1. The configurational entropy of the high entropy Prussian blue analog material prepared in this embodiment is S conf = 1.62R, its configuration entropy is greater than 1.5R, and it is a high entropy material.
[0036] Comparative Example 1 The preparation method of the Prussian blue analog CuCoNiCrMn-PBA in this comparative example is substantially the same as that in Example 1, except that the mixture in step 5 is not subjected to the Oswald ripening process.
[0037] Comparative Example 2 The preparation method of the Prussian blue analogue CuCoNiCrMn-PBA in this comparative example is basically the same as that in Example 1, except that the pH value of the transition metal solution in step 1 is 5, and in the prepared Prussian blue analogue, the transition metal ions have undergone precipitation reaction before coprecipitation.
[0038] Comparative Example 3 The preparation method of the Prussian blue analogue CuCoNiCrMn-PBA in this comparative example is basically the same as that in Example 1, except that the pH value of the transition metal solution in step 1 is 7, and in the prepared Prussian blue analogue, the transition metal ions have undergone precipitation reaction before coprecipitation.
[0039] Example 4 1. The SEM results of the high entropy Prussian blue analogue prepared in Example 1 are as follows: Figure 1 As shown, the SEM results of the Prussian blue analogue prepared in Comparative Example 1 are as follows Figure 2 As shown, by comparing the SEM images, it can be found that the crystals of the high entropy Prussian blue analogue prepared in Example 1 are more regular.
[0040] 2. The Prussian blue analogues obtained in Example 1 and Comparative Example 1 were respectively mixed with conductive carbon and binder PVDF in a mass ratio of 7:2:1 to prepare electrode sheets, and a half-cell was assembled with a sodium sheet as the counter electrode. The electrolyte formula was: 1 M NaClO 4 in DMC:EC:PC=1:1:1 Vol% with 5% FEC.
[0041] (1) The CV curve of the high entropy Prussian blue analogue prepared in Example 1 as the positive electrode active material of the sodium ion battery in the half-cell is shown in FIG. Figure 3 As shown, the CV curve of the Prussian blue analogue prepared in Comparative Example 1 as the positive electrode active material of the sodium ion battery in the half-cell is as follows Figure 4 As shown, by comparing the CV curves, it can be found that the high entropy Prussian blue analogue obtained in Example 1 undergoes a sufficient redox reaction, the redox peak is more obvious, and the reversibility is better.
[0042] (2) Cyclic performance of the high-entropy Prussian blue analogue prepared in Example 1 as a positive electrode active material for sodium-ion batteries in a half-cell (100 mA g -1 and 1 A g -1 )like Figure 5 and Figure 6 As shown in the figure, the cycle performance diagram of the Prussian blue analogue prepared in Comparative Example 1 as a positive electrode active material for sodium ion batteries in a half-cell (100 mA g -1 and 1 A g -1 )like Figure 7 and Figure 8 By comparing the cycle performance diagram, it can be found that the high entropy Prussian blue analogue obtained in Example 1 has a higher initial specific capacity (126.2 mAh g -1 ), the capacity retention rate is 80% after 100 cycles, which has better cycle stability.
[0043] (3) The rate performance of the high entropy Prussian blue analogue prepared in Example 1 as a positive electrode active material for sodium ion batteries in a half-cell is shown in the figure below: Fig. 9 As shown, the rate performance of the Prussian blue analogue prepared in Comparative Example 1 as a positive electrode active material for a sodium ion battery in a half-cell is shown in FIG. Fig.10 As shown in the rate performance diagram, it is found that the high entropy Prussian blue analogue obtained in Example 1 has excellent rate performance after cycling at different current densities and then returning to the initial current density, with a stable specific capacity.
[0044] Although the above embodiments have been described in detail, they are only a part of the embodiments of the present invention, not all of them. People can also obtain other embodiments based on this embodiment without creativity, and these embodiments all belong to the protection scope of the present invention.
Claims
1. A method for preparing a high entropy Prussian blue analog material CuCoNiCrMn-PBA, characterized in that: The following steps are involved: (1) dissolving copper salt, cobalt salt, nickel salt, chromium salt, manganese salt and sodium citrate in deionized water, adjusting the pH to 2-3, and obtaining a transition metal solution; (2) dissolving sodium ferrocyanide and sodium chloride in deionized water to obtain a sodium ferrocyanide salt solution; (3) adding the transition metal solution and the sodium ferrocyanide salt solution dropwise into deionized water while stirring to perform co-precipitation; (4) After the coprecipitation is completed, ascorbic acid is added to obtain a mixture; (5) The mixture is subjected to an Oswald ripening process and centrifuged to obtain a precipitate, thereby obtaining a high entropy Prussian blue analog material CuCoNiCrMn-PBA; The conditions of the Oswald ripening process are: the mixture is placed in an environment of 60-100° C. and allowed to stand for 24 h; the particle size of the high entropy Prussian blue analog material CuCoNiCrMn-PBA is 0.5-1 μm; The copper salt is copper sulfate pentahydrate, the cobalt salt is cobalt sulfate heptahydrate, the nickel salt is nickel sulfate hexahydrate, the chromium salt is chromium sulfate hexahydrate, and the manganese salt is manganese sulfate monohydrate.
2. The preparation method according to claim 1, characterized in that: In the step (1), the molar concentration of the transition metal element is 2.625-4.2 mmol / L, and the molar ratio of the copper salt, the cobalt salt, the nickel salt, the chromium salt and the manganese salt in the transition metal element is 1:1:1:1:1-4; The molar ratio of transition metal element to sodium citrate is 1:3-5; The pH was adjusted to 3 using 0.1 mol / L dilute hydrochloric acid.
3. The preparation method according to claim 2, characterized in that: In the transition metal solution, the molar concentration of the transition metal element is 3 mmol / L, and among the transition metal elements, the molar ratio of copper salt, cobalt salt, nickel salt, chromium salt and manganese salt is 1:1:1:1:1.71; The molar ratio of the transition metal element to sodium citrate is 1:
5.
4. The preparation method according to claim 1, characterized in that: In the step (2), the molar ratio of sodium ferrocyanide to sodium chloride is 1:20-25, and the molar ratio of the transition metal element to sodium ferrocyanide is 1:1.2-2.
5. The preparation method according to claim 4, characterized in that: The molar ratio of the sodium ferrocyanide to sodium chloride is 1:25, and the molar ratio of the transition metal element to the sodium ferrocyanide is 1:1.
6.
6. The preparation method according to claim 1, characterized in that: In the step (3), the dripping speed is 1 drop per second, and 3 to 5 drops of sodium ferrocyanide salt solution are first dripped, and then the transition metal solution and the sodium ferrocyanide salt solution are dripped simultaneously; In the step (4), the molar ratio of ascorbic acid to transition metal element is 3.79:
1.
7. An electrode sheet, characterized in that: The electrode sheet comprises the high entropy Prussian blue analog material CuCoNiCrMn-PBA prepared by the preparation method as claimed in claim 1.
8. A sodium ion battery, characterized in that: The sodium ion battery comprises the electrode sheet as claimed in claim 7.
Citation Information
Patent Citations
High-entropy Prussian blue material and preparation method thereof
CN113690433A
Medium-entropy sodium ion battery positive electrode material and preparation method thereof
CN116354364A
Preparation method and application of mesoporous high-entropy Prussian blue-based positive electrode material of sodium-ion battery
CN117776216A
Cited By
High-entropy Prussian blue analogue as well as preparation method and application thereof
CN121948491A